The improbability principle : why coincidences, miracles, and rare events happen every day - Hand, D. J. 1950- (Scientific American/Farrar, Straus and Giroux, 2014)
"An eye-opening and engrossing look at rare moments, why they occur, and how they shape our world In The Improbability Principle, the renowned statistician David J. Hand unveils his groundbreaking argument that extraordinarily rare events are in fact commonplace. Weaving together fascinating new ways to think about chance, Hand highlights his "law of near enough," the "look elsewhere effect," and more, doing for probability what Newton's laws of motion did for mechanics. Through humorous and engaging tales of two-time lottery winners, gambling gone wrong, and bizarre coincidences that we can't quite fathom, Hand argues that extremely unlikely events must happen, and no mystical or supernatural explanation is necessary to understand why. Hand's investigation, grounded in statistics and brought to life with fascinating anecdotes, finally explains "unexplainable" events such as unexpectedly bumping into a friend in a foreign country and coming across an unfamiliar word twice in one day. Along the way, we learn what the Bible and Shakespeare have in common, just how to win the lottery, why financial crashes are par for the course, and why lightning does strike the same place (and the same person) more than once. As Hand makes clear, we can rest assured that we'll experience a "miracle" roughly once per month. An irresistible adventure into the laws behind chance moments, The Improbability Principle transforms how we think about business decisions, everyday encounters, serendipity, and luck"--